Meetings, bloody meetings. - Video Arts. (Tuxedo, N.Y. : Video Arts, 1976)
Illustrates the basic principles for conducting more productive meetings.
With booklet: How to run a meeting.
Director, Peter Robinson; writers, John Cleese, Antony Jay.
Keywords: Meetings; Communication in management